Quantum-inspired cognitive agents - Huber-Liebl, Markus; Römer, Ronald; Wirsching, Günther; Schmitt, Ingo; beim Graben, Peter; Wolff, Matthias (Frontiers in Applied Mathematics and Statistics, 2022)
The concept of intelligent agents is—roughly speaking—based on an architecture and a set of behavioral programs that primarily serve to solve problems autonomously. Increasing the degree of autonomy and improving the cognitive performance are two important research trends. The degree of autonomy can be increased using higher-level psychological modules with which needs and motives are taken into account. In our approach we integrate these modules in an architecture for a multi-agent system, such that distributed problem solutions can be achieved. Further, after uncovering some weaknesses in the cognitive performance of traditionally designed agents, we focus on two major aspects. On the one hand, the knowledge processing of cognitive agents is based on logical formalisms, which have deficiencies in the representation and processing of incomplete or uncertain knowledge. On the other hand, in order to fully understand the performance of cognitive agents, explanations at the symbolic and subsymbolic level are required. Both aspects can be addressed by quantum-inspired cognitive agents. To investigate this approach, we consider two tasks in the sphere of Shannon's famous mouse-maze problem: namely classifying target objects and ontology inference. First, classification of an unknown target object in the mouse-maze, such as cheese, water, bacon, is based on sensory data that measure characteristics like odor, color, shape, or nature. For an intelligent agent we need a classifier with good prediction accuracy and explanatory power on a symbolic level. Boolean logic classifiers do work on symbolic level but are not adequate for dealing with continuous data. Therefore, we demonstrate and evaluate a quantum-logic-inspired classifier in comparison to Boolean-logic-based classifiers. Second, ontology inference is iteratively achieved by a quantum-inspired agent through maze exploration. This requires the agent to be able to manipulate its own state by performing actions and by collecting sensory data during perception. We suggest an algebraic approach where both kinds of behaviors are uniquely described by quantum operators. The agent's state space is then iteratively constructed by carrying out unitary action operators, while Hermitian perception operators act as observables on quantum eigenstates. As a result an ontology emerges as the simultaneous solution of the respective eigenvalue equations.